The Possibility of “Inference Causation”: Inferring Cause-in-Fact and the Nature of Legal Fact-Finding - Brown, Russell (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2010)
This article defends what it refers to as “inference causation”: a fact-finder’s drawing of a causal link between a defendant’s actions and a plaintiff’s suffering in tort claims in the absence of expert scientific evidence.This type of reasoning, affirmed in 1990 by Justice Sopinka in the Supreme Court of Canada decision, Snell v. Farrell, has encountered significant academic criticism. The author defends inference causation by considering evidence theory. First, he shows that inference causation forms a part of law’s veritism—its commitment to the truth—since legal fact-finding’s aim is always to seek out the best obtainable truth, rather than the absolute truth. Second, he critiques the primacy of scientific evidence by showing that both its reasoning process and the nature of its conclusions are different from those of legal fact-finding. Last, the author shows that all fact-finding—particularly all legal fact-finding—is already inferential. Scientific evidence forms but one of many different elements that are analyzed by fact-finders in their inference about which factual account of the disputed events is the best account. Accordingly, where none is available, the same inference of fact is nonetheless possible.